If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.75y = 2x + -6 Reorder the terms: 0.75y = -6 + 2x Solving 0.75y = -6 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '0.75'. y = -8 + 2.666666667x Simplifying y = -8 + 2.666666667x
| 2(y+2)-8=0 | | -4x^2+19x=-320 | | x+1-4x=13 | | 5/8q=-20 | | 8x-13y=12 | | Y-5=m(x-6)form | | -18=-x-11 | | 8y+y^2=180 | | 8y+y^2=189 | | 0.54(6)+.06x=.18(24+x) | | f(4)=9x+7 | | -8+6x+4x=-98 | | 13x+1=9x+5 | | 3(c-63)=27 | | 5x-9+3x=87 | | f(5)=3x+x^2 | | (X-2)/10=(x-7)/5 | | X+325=520 | | f(x)=3x+x^2 | | 4x+10-2x=-10 | | 3(k+9)=72 | | -t+-6=-10 | | 32(x-1)+115x+10(x+2)=1607 | | -24=8(r+63) | | 43=2x+2x+7 | | 3/7x3 | | 3h+2=-4 | | -2x-2+5x=16 | | 4(b-73)+44=60 | | 7-3m=13-5m | | p=15x-1000 | | 20=5+3m |